2003
DOI: 10.1097/01.shk.0000051758.08171.bc
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Growth Hormone Increases Thyroid Hormone-Binding Sites in Recovering Severely Burned Children

Abstract: Thyroxine (T4), Tri-iodothyronine (T3), and total serum protein levels are reduced in severely burned children. T4 and T3 are carried on serum transport proteins via thyroid hormone-binding sites (THBS). Treatment of bums with recombinant human growth hormone (rhGH) increases albumin (Alb) and prealbumin (PreAlb), which bind nearly 30% of circulating T4 and T3. This study investigated the effect of rhGH on THBS sites in burned children. Records of 11 acutely burned children with a total body surface area burne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…These few studies report that thyroid hormones are low following burn injury, as in adults 32,33 . Thyroid hormones are reported to fall, especially in major burns, possibly due to the body's metabolic adaptation 34 .…”
Section: Discussionmentioning
confidence: 94%
“…These few studies report that thyroid hormones are low following burn injury, as in adults 32,33 . Thyroid hormones are reported to fall, especially in major burns, possibly due to the body's metabolic adaptation 34 .…”
Section: Discussionmentioning
confidence: 94%
“…The intensity of the transthyretin peak increased in the low-responder group and decreased in the high-responder group during GH treatment. Interestingly, GH administration has also been shown to increase serum levels of transthyretin in severely burned children and in adults after hepatectomy [ 15 , 16 ], suggesting a common mechanism between serious illness and low GH responsiveness. Our results are in line with a report showing that serum levels of transthyretin in rats were markedly decreased by hypophysectomy and further decreased after GH replacement [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results have been published about the effect of rhGH on the healing time of donor sites. (79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92) Kim and colleagues studied adults with full thickness burns greater than 20% TBSA and showed that treatment with rhGH for 3 months during rehabilitation phase increases fitness levels, muscle power and metabolic processes. (93) Growth hormone supplementation and mortality have been the focus of debate in the literature.…”
Section: Recombinant Human Growth Hormone (Rhgh)mentioning
confidence: 99%